EVALUATION OF CLINICAL COURSE AND OUTCOMES IN ZONE I RETINOPATHY OF PREMATURITY IN A TERTIARY CARE INSTITUTE - PARMAR, BHAWNA; SOM, VIVEK; DUBEY, ADITI (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The objectives are to study the clinical course and outcomes of Zone I retinopathy of prematurity and also to study the indication of management and the factors affecting the choice of treatment modality. Methods: The present study was a prospective observational study conducted at the Department of Ophthalmology. All the neonates having Zone I retinopathy of prematurity (ROP) at presentation according to the International Classification of ROP classification were included in the study after obtaining permission from the institutional ethics committee and consent from parents. Results: In the present study, 526 neonates were screened and ROP was detected in 131 neonates with an incidence of 24.90%. Out of those 131, Zone I ROP was detected in 50 neonates, giving an incidence of 9.50%. Conclusion: In our study, Type 1 ROP has a variable course with 47.61% who initially had mild-looking disease developed Type 1 ROP requiring treatment. Hence, a proper timely follow-up is also important in these patients, we cannot exclude the probability of ROP based on the first examination, because when they are present, they are very preterm so vascularization is only until Zone I.